2004
DOI: 10.1177/0891243203259133
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Work

Abstract: How do adolescent girls envision the world of work and their potential place in it? This article considers teen magazines as a possible source for girls' perceptions about the work world, including their own career futures. The author explores the occupational landscape embedded within Seventeen magazine in 1992 in both quantitative and qualitative terms. The labor market in Seventeen-land is heavily skewed toward professional occupations, particularly in the entertainment industry. A close reading of the text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Magazines, such as Seventeen, were identified as part of the "common culture" of adolescents, suggesting that the magazine not only dictates how the girls should look (body image) but also "what women should not do, be or think" (Massoni, 2004, p. 49). Massoni's (2004) research resulted in helping to identify that the printed media can dictate career choices in a manner which has not been fully examined. She found that "controlling images" such as "the Cinderellas, Barbies, and Girl Fridays" are permeating the pages of Seventeen (Massoni, 2004, p. 63).…”
Section: Career Development Theories For Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Magazines, such as Seventeen, were identified as part of the "common culture" of adolescents, suggesting that the magazine not only dictates how the girls should look (body image) but also "what women should not do, be or think" (Massoni, 2004, p. 49). Massoni's (2004) research resulted in helping to identify that the printed media can dictate career choices in a manner which has not been fully examined. She found that "controlling images" such as "the Cinderellas, Barbies, and Girl Fridays" are permeating the pages of Seventeen (Massoni, 2004, p. 63).…”
Section: Career Development Theories For Womenmentioning
confidence: 99%
“…However, the researchers did emphasize that strides have been made, including recognizing the complexity of women's career paths and that their paths are different from men. Massoni (2004) addressed the lack of research concerning the implications of media images on career aspirations of young girls. The researcher indicated that although there has been a significant amount of study concerning the impact of media images on the body image of young women, there is a gap in the literature concerning the effect those same images have on the career choices of the girls.…”
Section: Career Development Theories For Womenmentioning
confidence: 99%